Interrelationship Between Lower Urinary Tract Symptoms, Diabetic Neuropathy, Early Renal Function Decline, and Psychological Distress in Adults with Metabolic Syndrome: A Cross-Sectional Study From Pakistan - Zeeshan Shaukat, Neesha, Mahboob Qadir, Ammad Ahmad Siddiqui, Shakil Asif, Faraz Ahmed (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
The growing prevalence of metabolic syndrome in South Asia has prompted concernregarding its complex multisystem consequences. Among these, lower urinary tract symptoms (LUTS), diabetic neuropathy